Monetary and financial integration in West Africa - Oshikoya, Temitope Waheed (London ; New York : Routledge, 2010)
This book examines the process, progress, prospects and challenges of forming a monetary union and of the ongoing financial integration among these five West Africa states.
Includes bibliographical references and index.
uaj 23/10/2013
Loans
Keywords: Monetary unions; Africa, West